Geochemical position of Pb, Zn and Cd in soils near the Olkusz mine/smelter, South Poland: effects of land use, type of contamination and distance from pollution source - Chrastný, Vladislav; Vaněk, Aleš; Teper, Leslaw; Cabala, Jerzy; Procházka, Jan; Pechar, Libor; Drahota, Petr; Penížek, Vít; Komárek, Michael; Novák, Martin (Environmental monitoring and assessment, 2012)
The soils adjacent to an area of historical mining, ore processing and smelting activities reflects the historical background and a mixing of recent contamination sources. The main anthropogenic sources of metals can be connected with historical and recent mine wastes, direct atmospheric deposition from mining and smelting processes and dust particles originating from open tailings ponds. Contaminated agriculture and forest soil samples with mining and smelting related pollutants were collected at different distances from the source of emission in the Pb-Zn-Ag mining area near Olkusz, Upper Silesia to (a) compare the chemical speciation of metals in agriculture and forest soils situated at the same distance from the point source of pollution (paired sampling design), (b) to evaluate the relationship between the distance from the polluter and the retention of the metals in the soil, (c) to describe mineralogy transformation of anthropogenic soil particles in the soils, and (d) to assess the effect of deposited fly ash vs. dumped mining/smelting waste on the mobility and bioavailability of metals in the soil. Forest soils are much more affected with smelting processes than agriculture soils. However, agriculture soils suffer from the downward metal migration more than the forest soils. The maximum concentrations of Pb, Zn, and Cd were detected in a forest soil profile near the smelter and reached about 25 g kg(- 1), 20 g kg(- 1) and 200 mg kg(- 1) for Pb, Zn and Cd, respectively. The metal pollutants from smelting processes are less stable under slightly alkaline soil pH then acidic due to the metal carbonates precipitation. Metal mobility ranges in the studied forest soils are as follows: Pb > Zn ≈ Cd for relatively circum-neutral soil pH (near the smelter), Cd > Zn > Pb for acidic soils (further from the smelter). Under relatively comparable pH conditions, the main soil properties influencing metal migration are total organic carbon and cation exchange capacity. The mobilization of Pb, Zn and Cd in soils depends on the persistence of the metal-containing particles in the atmosphere; the longer the time, the more abundant the stable forms. The dumped mining/smelting waste is less risk of easily mobilizable metal forms, however, downward metal migration especially due to the periodical leaching of the waste was observed.
Keywords: půda; Metals, Heavy; Mining; monitorování životního prostředí; Poland; chemická frakcionace; Chemical Fractionation; Soil; látky znečišťující půdu; Polsko; Environmental Monitoring; Soil Pollutants; těžké kovy; hornictví